The Dynamics of Financial Management of The Village in Sugian Village Sambelia District East Lombok - Hapizah, Hidayatul; Juaini, Muhammad; Mispandi, Mispandi (Sumber Belajar Sejahtera, 2024)
This research aims to figure out how the dynamics carried out by the village government in managing the allocation of village funds (ADD) are formed both at the level of refinancing, implementation, and accountability. This research uses qualitative methods. The data in this study was obtained through observations, interviews, and documentation. The data is then analyzed by reducing it, presenting it, and drawing conclusions. As for the results of this study, it shows that the Sugian village government manages the village budget, which includes the village fund allocation (ADD), well and makes changes at every level.During the planning phase of the village government, Sugian made changes by holding the Musyawarah Plan (MUSREN) with the invitation of various parties, such as the village government, the village forestry agency (BPD), religious figures, public figures, youth, and corals. In the statement, the village government provided detailed information on the amount of funds received, the sources of the funds, and the plans for the use of those funds. As for the form of change in the implementation stage, which is to install banners and create a website that informs about the activities financed by the village fund allocation, As for changes in the level of responsibility, it is to make some reports, such as accountability letters (SPJ), receipts, payment order letters, invoices, activity reports, and photos of activities. The reports are submitted to the BPD, the PMD, and the Inspectorate.